Use of modified Blaney and Criddle formula for Estimating water requirements - RAO, K. SUBBA; YAZDANI, G. (MAUSAM, 1981)
Experimental values of crop growth stage coefficients (Kc) were determined for paddy and sugarcane using lysimetric data recorded at Canning. Nellore, Annamalainagar and Anakapalle. Kc varies with the type of the crop, location and season. The seasonal variation of Kc is similar to potential evapotranspiration (PET).